How Prevalent Is Downward Rigidity in Nominal Wages? International Evidence from Payroll Records and Pay Slips - Michael Elsby; Gary Solon (Institute of Labor Economics (IZA), 2019)
For more than 80 years, many macroeconomic analyses have been premised on the assumption that workers' nominal wage rates cannot be cut. Contrary evidence from household surveys reasonably has been discounted on the ground that the measurement of frequent wage cuts might be an artifact of reporting error. This article summarizes a more recent wave of studies based on more accurate wage data from payroll records and pay slips. By and large, these studies indicate that, except in extreme circumstances (when nominal wage cuts are either legally prohibited or rendered beside the point by very high inflation), nominal wage cuts from one year to the next appear quite common, typically affecting 15-25 percent of job stayers in periods of low inflation.
Keywords: J3; E24; 330; nominal wage rigidity; payroll records